Blockchain-Enabled Secure Data Sharing Framework for Healthcare IoT Devices - Jing, Qi (International Journal of Engineering, Science and Information Technology, 2025)
Medical data security challenges have increased dramatically because healthcare institutions continue to integrate more Internet of Things devices to deliver data-driven clinical services. Access control systems based on RBAC, ABAC and MAC do not meet the requirements of flexible protection and scalable and context-aware security which are needed for dynamic healthcare environments. The research objective focuses on creating a resilient decentralized access control solution which delivers secure time-sensitive access permissions in healthcare IoT systems. A blockchain-based hybrid access control framework with RBAC and ABAC provides the solution to meet this requirement. A dual mechanism of smart contracts and IPFS storage runs the model while variables and user-facing elements shift based on environmental characteristics and individual circumstances. Results from experimental evaluation show that this proposed framework delivers 96.5% access precision together with policy evaluation times below 3.2 ms and 120 ms response times while handling 74 transactions per second while remaining affordable at $2.1 and demanding 45 to 52 MB from critical system memory. The obtained results demonstrate better scalability together with enhanced performance and adaptability when compared to using ABAC, RBAC and MAC singularly. Healthcare IoT systems should implement a blockchain-based hybrid access control system as an optimal method to secure data sharing in real-time resource-constrained scenarios.